TANGGUNG JAWAB DARI TANGGUNG GUGAT HUKUM PENGOBATAN ALTERNATIF AKUPUNTUR - Meivy Isnoviana; Suhandi Suhandi (Perspektif, 2006)
Nowadays, awareness of healthy life is increasing tremendously. That makes people try every way to find the best thing for their health. A method that attracts many peoples attention is alternative treatment such as acupuncture. The method developing in acupuncture treatment is maintaining bio-energy balance in human body. This, accordingly has increased the number of acupuncturist. The government in this matter has anticipated with the regulation as stated in UU No. 23 of Health, especially ps. 47 and PERMENKES RI No. 1076/SK/VII/2003 of Traditional Treatment. This is aimed to minimize the unwanted cases.